PROSPECTS FOR IMPROVING THE DEPOSIT POLICY OF COMMERCIAL BANKS - Shermukhamedov Bekhzodjon Usmonovich; Abdulatifova Mohinur Alisher qizi (American Journals, 2023)
This article discusses the trends observed in the implementation of deposit policy by commercial banks and issues related to their impact on deposit policy. In the article, the deposit policy is a key part of the overall banking policy, which defines the strategy and tactics of commercial banks to conduct deposit activities. It also contains the author's suggestions and recommendations on the problems of deposit policy and their solutions
Keywords: deposit, deposit types, demand deposit, term deposit, savings deposit, transactional deposit, certificate of deposit, bank resources, deposit policy, attracted funds, bank resource base.